Assessment of PCR in the detection of Leishmania spp in experimentally infected individual phlebotomine sandflies (Diptera: Psychodidae: Phlebotominae) - MICHALSKY, Érika M.; FORTES-DIAS, Consuelo L.; PIMENTA, Paulo F.P.; SECUNDINO, Nágila F.C.; DIAS, Edelberto S. (Revista do Instituto de Medicina Tropical de São Paulo, 2002)
DNA amplification by the polymerase chain reaction (PCR) was applied in the investigation of the presence of Leishmania (Kinetoplastida: Trypanosomatidae) parasites in single phlebotomine sandflies. Three phlebotomine/parasite pairs were used: Lutzomyia longipalpis/Leishmania chagasi, Lutzomyia migonei/Leishmania amazonensis and Lutzomyia migonei/Leishmania braziliensis, all of them incriminated in the transmission of visceral or cutaneous leishmaniasis. DNA extraction was performed with whole insects, with no need of previous digestive tract dissection or pooling specimens. The presence of either mouse blood in the digestive tract of the sandflies or the digestive tract itself did not interfere in the PCR. Infection by as few as 10 Leishmania sp. per individual were sufficient for DNA amplification with genus-specific primers. Using primers for L. braziliensis and L. mexicana complexes, respectively, it was possible to discriminate between L. braziliensis and L. amazonensis in experimentally infected vectors (L. migonei).